KEPEMIMPINAN TRANSFORMASIONAL BERBASIS NILAI ISLAM: STRATEGI PENINGKATAN KUALITAS PEMBELAJARAN DI SEKOLAH SMA MIFTAHUL ULUM - Arifin, Syamsul; Wahab, Wahab; Prabowo, Sugeng Listyo (Jurnal Visi Ilmu Pendidikan, 2026)
This study examines the application of transformational leadership by the principal of SMA Miftahul Ulum, an Islamic secondary school located in the rural area of Kubu Raya Regency, West Kalimantan, in an effort to enhance the quality of learning amidst limited resources. Using a qualitative case study approach, the research relied on interviews, observations, and document analysis. The findings reveal that the principal successfully implemented the four dimensions of transformational leadership idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration adapted through an Islamic perspective and local strategies. These strategies included optimizing the school"™s budget and actively involving the surrounding community. This implementation led to increased teacher motivation and the emergence of innovative teaching practices. Nevertheless, challenges such as salary delays and generational gaps remained. The study contributes theoretically by proposing a fifth dimension of transformational leadership based on Islamic values and offers practical recommendations for educational leaders and policymakers, particularly in rural settings.